ANALYSIS OF EMPLOYEE'S WORK DISCIPLINE IN PT CIPTA PEDAGANG UNGGUL FROM MOTIVATION AND LEADERSHIP STYLE - Nur Affini, Dinar (Dinasti Publisher, 2021)
This study aims to analyze the influence of motivation and leadership style on employee’s work discipline. The population in this study were 30 employees of PT. Cipta Pedagang Unggul. The sample used was 30 employees of PT. Cipta Pedagang Unggul with saturated sample method. The data used are primary data from observations, questionnaires, and interviews. The research instrument is a questionnaire. Data analysis method using Likert scale, processed using SPSS. This study proves that motivation has no significant effect on employee discipline. Leadership style has a positive and significant effect on employee discipline.